IACHR warns of erosion to women’s and LGBTQ+ rights, memory policies in Argentina - Jaureguy, Martina (Buenos Aires Herald, 2025)
In its annual report, the human rights watchdog for the Americas expressed concern about President Milei’s austerity measures and violent discourse. The IACHR observed “setbacks in memory, truth and justice policies” including layoffs in the Human Rights Secretariat and the closure of programs and specialized entities.